WOMAN’S POSITION IN UNDOCUMENTED MARRIAGES - Arsal, Thriwaty (Komunitas, 2014)
The term of undocumented marriage is only known in Muslim community in Indonesia. Undocumented marriage is a legal type of marriage based on Islam as long as it is meets the marriage’s legal requirements; however, it is diverge from the state rules because it is not registered in the authorized institution for marriage. A woman who married with this type of marriage, based on law and administration, has no clear identity before the state. It will make her difficult to have her right as a wife. Undocumented marriage will give weak position for children by law. In addition, women’s position in this type of marriage is the disadvantage object. Although undocumented marriage has negative impact especially on women and children; in Warurejo, however, this marriage is widely dispersed among the community. Research is conducted in Warurejo village, East Java using qualitative, quantitative and semantic approaches. Research result shows that the women’s position in this undocumented marriage is having discrimination, subordination, no bargaining power in the family, and susceptible for cervix cancer. They do not have any option for the future because it is determined by family, norm and value system prevailed in the community. Istilah nikah siri hanya dikenal pada masyarakat muslim Indonesia. Nikah siri adalah bentuk pernikahan yang sah secara agama Islam sepanjang memenuhi syarat sahnya pernikahan tapi dianggap menyimpang dari peraturan negara karena tidak terdaftar pada lembaga yang berwenang mengurusi masalah perkawinan. Perempuan yang nikah siri, secara catatan hukum atau administrasi tidak memiliki identitas yang jelas di hadapan negara. Sulit untuk mendapatkan hak-haknya sebagai seorang istri. Pernikahan siri berdampak pula pada kelemahan posisi anak secara hukum. Selain itu, posisi perempuan dalam nikah siri juga lebih banyak menjadi objek yang dirugikan. Walaupun nikah siri mempunyai dampak negatif khususnya terhadap perempuan dan anak tapi di Warurejo nikah siri begitu berkembang dan meluas pada masyarakat. Lokasi penelitian dilakukan di desa Warurejo Jawa Timur dengan menggunakan pendekatan kualitatif, kuantitatif dan semantik. Hasil penelitian menunjukkan bahwa posisi perempuan dalam menikah siri mengalami diskriminasi, subordinasi, tidak memiliki posisi tawar dalam keluarga, rentan terhadap kanker serviks. Perempuan tidak memiliki pilihan untuk menentukan masa depannya karena masa depannya ditentukan oleh keluarga dan norma dan sistem nilai yang berlaku pada masyarakat tersebut